Strategi Promosi Wisata Dalam Mendorong Investasi: Studi Pengembangan Destinasi Pulau Di Kota Makassar - Miarni, Isra; Basid, Abdul; Annas, Aswar (Universitas Muhammadiyah Mataram, 2025)
This study examines the Makassar City government's strategic program in promoting island tourism, identifying the inhibiting and supporting factors that arise, and examining regional investment through tourism promotion. This study uses a qualitative approach with data collection sourced from interviews, documentation, observation, and document review. The data obtained were then coded with Nvivo 12 Plus. The results of the study indicate that the government's strategic steps related to island tourism promotion include branding and destination image, holding events and festivals, providing integrated tourism packages, improving information services, and using digital promotional media. The hampered tourism promotion activities are caused by inadequate infrastructure and low public awareness. To overcome this, the government needs to provide clean water infrastructure, provide bathrooms to meet tourist needs, provide trash bins, educate the public, and improve the security of tourist locations. Meanwhile, supporting factors include the presence of strong local community participation and the use of digital platforms as promotional media. Increasing regional investment through tourism promotion includes expanding creative economic opportunities and MSMEs, creating new jobs, and increasing local revenue.